2023
DOI: 10.3389/fendo.2023.1087053
|View full text |Cite
|
Sign up to set email alerts
|

Cell non-autonomous regulation of cerebrovascular aging processes by the somatotropic axis

Abstract: Age-related cerebrovascular pathologies, ranging from cerebromicrovascular functional and structural alterations to large vessel atherosclerosis, promote the genesis of vascular cognitive impairment and dementia (VCID) and exacerbate Alzheimer’s disease. Recent advances in geroscience, including results from studies on heterochronic parabiosis models, reinforce the hypothesis that cell non-autonomous mechanisms play a key role in regulating cerebrovascular aging processes. Growth hormone (GH) and insulin-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 343 publications
0
7
0
Order By: Relevance
“…There is growing evidence that age-related impairments in the structure and function of the cerebral microcirculation are causally linked to cognitive decline. 8,15,48,[55][56][57][58][59][60][61][62][63] Our findings highlight the critical impact of anti-geronic IGF-1 signaling on cerebromicrovascular endothelial cells and underline its significance in maintaining the functional and structural integrity of the cerebral microcirculatory system.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…There is growing evidence that age-related impairments in the structure and function of the cerebral microcirculation are causally linked to cognitive decline. 8,15,48,[55][56][57][58][59][60][61][62][63] Our findings highlight the critical impact of anti-geronic IGF-1 signaling on cerebromicrovascular endothelial cells and underline its significance in maintaining the functional and structural integrity of the cerebral microcirculatory system.…”
Section: Discussionmentioning
confidence: 59%
“…IGF1R deletion in these cells could have some level of indirect outcomes on brain vascular endothelial cells. Based on our recently published results, circulating factors have striking effect on the vasculature, especially on endothelial cells; thus, it is very difficult to completely dissect these mechanisms in a living organism; therefore, we were focusing on the brain endothelium‐related consequences 55,100 . It is also important to mention that it is still unclear which brain vascular region is the most effected by endothelial senescence in this accelerated aging model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors contribute to cognitive impairment, balance and mobility defects, and other adverse consequences. Extensive evidence has demonstrated the role of the somatotropic axis in cerebrovascular aging, in particular, a role for insulin-like growth factor 1 (IGF-1) ( Bickel et al, 2023a ). IGF-1 is mainly produced by the liver, but also within the brain, and levels decrease with age.…”
Section: Introductionmentioning
confidence: 99%
“…VSMC phenotypic changes are also a part of the vascular response in cerebrovascular diseases such as ischemic and hemorrhagic stroke ( Chen et al, 2013 ; Poittevin et al, 2014 ; Wu et al, 2016 ). Growth factors, including IGF-1, are key regulators of VSMC phenotypic switching, for example IGF-1 plays a protective role in atherosclerotic plaque stability through its actions on VSMCs, and we recently demonstrated that IGF-1 induces cellular hypertrophy and altered expression of ECM genes and ECM remodeling genes in cultured primary rat VSMCs ( Risinger et al, 2006 ; von der Thusen et al, 2011 ; Fulop et al, 2019b ; Bickel et al, 2023a , b ). A potential role for IGF-1 on brain VSMCs is highlighted by our previous studies showing that mice with circulating IGF-1 deficiency exhibit pathological cerebrovascular arterial wall ECM remodeling in response to hypertension and impaired cerebrovascular autoregulation ( Fulop et al, 2019b ).…”
Section: Introductionmentioning
confidence: 99%